Continuous wave ultraviolet frequency upconversion due to triads of Nd3+ ions in fluoroindate glass - Menezes, L. de S; Araújo, Cid B. de; Maciel, G. S.; Messaddeq, Younes [UNESP]; Aegerter, M. A. (AIP Publishing, 1997)
We have observed ultraviolet upconversion fluorescence from the 4D3/2 and 2P3/2 levels of Nd3+ in fluoroindate glass under infrared pumping. It was found that the excitation of a large population in the 4F3/2 metastable level allows to achieve strong upconversion emissions at 354 and 382 nm. A simple rate equation model reproduces the temporal behavior of the upconverted emission and allows us to estimate the energy transfer rate among three Nd3+ ions participating in the process. © 1997 American Institute of Physics.